Progressive mitochondrial dysfunction impairs visual signal transduction and induces retinal degeneration in Drosophila - Cao, Jinguo; Li, Yining; Hu, Xiaohui; Wu, Zhaoqi; Zhang, Jiting; Zhou, Yue; Luan, Wei; Hu, Wen; Tang, Jianhong (Frontiers in Insect Science, 2025)
Mitochondrial dysfunction is closely associated with the pathogenesis of retinitis pigmentosa (RP), often through the generation of reactive oxygen species (ROS), which disrupts visual signal transduction. However, in certain instances, mitochondrial dysfunction does not correlate with an increase in ROS, and the precise mechanisms by which mitochondrial dysfunction contributes to RP remain poorly understood. In this study, we demonstrate that mitochondrial dysfunction can also impair visual signal transduction through ROS-independent mechanisms. Specifically, we identify that mitochondrial dysfunction affects key processes in phototransduction, including activation and bleaching, leading to the degradation of photoreceptor proteins and, ultimately, retinal degeneration. Our findings reveal that mitochondrial dysfunction influences RP through multifaceted pathways, underscoring its role in both hereditary and age-related forms of visual diseases. This study enhances our understanding of the molecular mechanisms underlying RP and establishes a novel model for investigating mitochondrial dysfunction in visual pathologies.